Advanced Functional Hybrid Proton Exchange Membranes Robust and Conductive at 120 °C. Issue 3 (1st December 2022) - Richard, Jason; Haidar, Fatima; Alzamora, Madeline K.; Maréchal, Manuel; Rovira, Natalia; Vacquier, Christophe; Sanchez, Clément; Laberty‐Robert, Christel
Abstract: Proton‐exchange membrane fuel cell vehicles offer a low‐carbon alternative to traditional oil fuel vehicles, but their performances still need improvement to be competitive. Raising their operating temperature to 120 °C will enhance their efficiency but is currently unfeasible due to the poor mechanical properties at high temperatures of the state‐of‐the‐art proton‐exchange membranes consisting of perfluorosulfonic acid (PFSA) ionomers. To address this issue, xx designed composite membranes made of two networks: a mat of hybrid fibers to maintain the mechanical properties filled with a matrix of PFSA‐based ionomer to ensure the proton conductivity. The hybrid fibers obtained by electrospinning are composed of intermixed domains of sulfonated silica and a fluorinated polymer. The inter‐fiber porosity is then filled with a PFSA ionomer to obtain dense composite membranes with a controlled fibers‐to‐ionomer ratio. At 80 °C, these obtained composite membranes show comparable performances to a pure PFSA commercial membrane. At 120 °C however, the tensile strength of the PFSA membrane drastically drop down to 0.2 MPa, while it is maintained at 7.0 MPa for the composite membrane. In addition, the composite membrane shows a good conductivity of up to 0.1 S cm −1 at 120 °C/90% RH, which increases with the ionomer content. Abstract : Composite hybrid membranes are designed to be mechanically stable and proton conductive at 120 °C. A first robust network of hybrid nanofibers is obtained by electrospinning and the porosity is further filled with a second network of perfluorosulfonic acid ionomer. The tensile strength at 120 °C is 35‐fold enhanced compared to a commercial ionomer membrane while showing good conductivity.